Jointly Building an Evaluation Culture: A Workshop Methodology for a European Project in the Field of Adult Education - Biffi, Elisabetta; Kritsotakis, George (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This paper presents a reflection on the role of cooperative research in addressing the topic of evaluation within the field of adult education. To this end, the authors outline a specific cooperation initiative that involved academics and practitioners from the field of adult education in different European countries.The project presented here is based on the hypothesis that in order to enhance evaluation at the European level, it is necessary to build a European culture of evaluation, which may be developed by creating a concrete space for collaboration among practitioners and researchers from a range of European adult education contexts.Specifically, the project wasdesigned to promote an exchange of experiences, expertise and practices among academic researchers and “practitioners” (Schön, 1983)involved in the evaluation of adult education. A key role was played by a Mobility Workshop: viewed as the core of the collaborative approach proposed, the Workshop provided a concrete opportunity for collaboration amongevaluators and researchers from different countries within Europe.